PERAN AKAD IJARAH DALAM BISNIS SYARIAH - MiLLAH; wulan lailatus azzahra; Achmad Fageh (Jurnal ini dipublikasikan oleh Pusat Penelitian dan Pengabdian Publikasi (P3M) STAI Nahdlatul Watan Samawa-licensed under a Creative Commons Attribution-ShareAlike 4.0 International License., 2022)
Many companies currently in Indonesia use the ijarah system in running a business that uses Islamic law, or sharia business. The number of companies that use sharia principles is due to avoid losses by both parties. The activities carried out in the ijarah contract described in the books of fiqh are that ijarah is a rental activity. Which is where in leasing, there is a wage in renting goods. In this study, the method we use is using a normative approach in which the authors collect primary and secondary data. the method used to describe and explain the application of the ijarah contract to the tailor service business which is reviewed in Islamic economics. The results of the study are analyzed using an inductive mindset, namely stating facts or facts that are specific in nature from the results of research on the application of the ijarah contract to the tailor service business, then explaining general theories or arguments about the ijarah contract in the tailoring service business, then analyzed using theory -the theory so that in the end a conclusion can be drawn